PERBEDAAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL KOOPERATIF JIGSAW DENGAN NHT DI SD - Rahayu, Kenny; Yunisrul, Yunisrul; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this  research is to find out difference result of math study between cooperative model  jigsaw type and NHT type. Type of this research is an experiment using quasi experiment design with pretest-posttest non-equivalent group. The total sample of research is 32 students in VA and VB class from SDN 10 2X11 Kayutanam Kabupaten Padang Pariaman,  whuch was selected by purposive sampling technique. Based on the results of data analysis using  t-test at a significance level of 0.05 where t count> t table is 3.0712> 1.69726 it can be concluded that the differences result between math study using cooperative model jigsaw type with NHT type. Keywords : Study result, Math,  Jigsaw,  NHT.